The Profile and Antimicrobial Activity of Bacillus Lipopeptide Extracts of Five Potential Biocontrol Strains - Dimkić, Ivica; Stanković, Slaviša; Nišavić, Marija; Petković, Marijana; Ristivojević, Petar; Fira, Djordje; Berić, Tanja (Frontiers in Microbiology, 2017)
In this study the efficacy of two different methods for extracting lipopeptides produced by five Bacillus strains-ethyl acetate extraction, and acid precipitation followed by methanol extraction—was investigated using mass spectrometry. High performance thin layer chromatography (HPTLC) was also used for the simultaneous separation of complex mixtures of lipopeptide extracts and for the determination of antimicrobial activity of their components. The mass spectra clearly showed well-resolved groups of peaks corresponding to different lipopeptide families (kurstakins, iturins, surfactins, and fengycins). The ethyl acetate extracts produced the most favorable results. The extracts of SS-12.6, SS-13.1, and SS-38.4 showed the highest inhibition zones. An iturin analog is responsible for the inhibition of Xanthomonas arboricola and Pseudomonas syringae phytopathogenic strains. HPTLC bioautography effectively identified the active compounds from a mixture of lipopeptide extracts, proving in situ its potential for use in direct detection and determination of antimicrobials. In the test of potential synergism among individual extracts used in different mixtures, stronger antimicrobial effects were not observed. Biochemical and phylogenetic analysis clustered isolates SS-12.6, SS-13.1, SS-27.2, and SS-38.4 together with Bacillus amyloliquefaciens, while SS-10.7 was more closely related to Bacillus pumilus.